Technology Utilization and Digital Literacy as Predictors of Learning Interest: Examining the Role of Self-Regulated Learning - Gunawan, Guntur; Yumiarty , Yuyun (International Journal of Electronics and Communications Systems, 2026)
This study examined the relationships among technology utilization, digital literacy, self-regulated learning (SRL), and students' learning interest, with SRL serving as a mediating variable. An explanatory cross-sectional survey design was employed, involving 150 students from the PGMI Study Program at IAIN Curup selected through simple random sampling. Data were collected using a five-point Likert-scale questionnaire measuring technology utilization, digital literacy, self-regulated learning, and learning interest. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4 with a bootstrapping procedure (add: 5,000 resamples, if applicable). The results showed that technology utilization was positively associated with self-regulated learning (β = 0.279, p = 0.001), while digital literacy was positively associated with self-regulated learning (β = 0.532, p = 0.000). Furthermore, self-regulated learning was positively associated with learning interest (β = 0.551, p = 0.000). Digital literacy demonstrated a positive direct association with learning interest (β = 0.179, p = 0.050), whereas technology utilization was not directly associated with learning interest (β = 0.081, p = 0.252). Indirect association analysis indicated that self-regulated learning fully mediated the relationship between technology utilization and learning interest and partially mediated the relationship between digital literacy and learning interest. The structural model explained 59.1% of the variance in self-regulated learning and 57.5% of the variance in learning interest. These findings highlight the important role of self-regulated learning in linking students' digital competencies and technology utilization with learning interest in higher education.